A shared tradition: transmitting maritime knowledge in print - Margaret E. Schotte (Asclepio: Revista de Historia de la Medicina y de la Ciencia)
As Europeans ventured more frequently on transoceanic voyages in the 16th century, it became essential for navigators to be able to carry out mathematical computations. Iberian educators rose to the occasion, developing textbooks and curricula to transmit these abstract concepts. At the same time that they strove to present new mathematical techniques, these maritime authors also captured the tacit skills that had been practiced for centuries. Thus, even though few working sailors put pen to paper, it is possible to recover aspects of their epistemology from these texts. Because books traveled so easily across borders, these academic sources also had far-reaching effects, inspiring similar educational programs across maritime Europe. This article recommends adopting a comparative perspective, since much can be learned by tracing the evolution of these shared practices as they traveled from Spain and Portugal to the Netherlands, France, and England, and back again.